Fishing community wireless network concept in Kuala Rompin, Pahang, Malaysia - Hashim, Wahidah; Ismail, Ahmad Fadzil; Mohd Radzi, Husni; Mohamed Salleh, Faridah; Ismail, Zurina; Mohamad, Zaleha (Blue Eyes Intelligence Engineering & Science Publication, 2019)
Fisheries communities are the main suppliers of Malaysian local maritime resources. These minority groups are synonym with low income, low education level, and plagued with a myriad of economic limitations. The article outlines a network infrastructure concept that deemed suited for fishing communities; designed based on surveys’ outcomes conducted on a group of fishermen in Kuala Rompin, Pahang, Malaysia. The survey outcomes were analysed using the induction method. System requirements are tabulated and the design of such concept is explained. The main motivation of the studies is that such a community to own their network that can facilitate the establishment of community resilience. The ideas where available resources are exploited in hope to improve the community’s living standard especially their household incomes. The fundamental concept of the system is directed towards three main elements; namely available technologies, community empowerment and cost-efficiency.